2007
DOI: 10.1007/s10658-007-9140-x
|View full text |Cite
|
Sign up to set email alerts
|

Parasitism of Trichoderma on Meloidogyne javanica and role of the gelatinous matrix

Abstract: Trichoderma (T. asperellum-203, 44 and GH11; T. atroviride-IMI 206040 and T. harzianum-248) parasitism on Meloidogyne javanica life stages was examined in vitro. Conidium attachment and parasitism differed beween the fungi. Egg masses, their derived eggs and second-stage juveniles (J2) were parasitized by Trichoderma asperellum-203, 44, and T. atroviride following conidium attachment. Trichoderma asperellum-GH11 attached to the nematodes but exhibited reduced penetration, whereas growth of T. harzianum-248 att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
73
0
6

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 127 publications
(85 citation statements)
references
References 26 publications
6
73
0
6
Order By: Relevance
“…These compounds act by various mechanisms like blocking molting of larvae, disrupting mating and sexual communication of nematodes, reducing the motility of gut and by inhibiting the formation of chitin [62]. Sharon et al [63] showed that eggs adhered with Trichoderma conidia became non-viable, thus decreasing the eclosion rate. In this study, the botanicals used only they were effective but when they were used in combination they show less effective so it is evident that as extract was diluted, toxicity was decreased resulting in correspondent decrease in inhibition and any inhibition was observed in distilled water.…”
Section: In Vitro Effect Of Botanicals and Trichoderma Harzianum Agaimentioning
confidence: 99%
“…These compounds act by various mechanisms like blocking molting of larvae, disrupting mating and sexual communication of nematodes, reducing the motility of gut and by inhibiting the formation of chitin [62]. Sharon et al [63] showed that eggs adhered with Trichoderma conidia became non-viable, thus decreasing the eclosion rate. In this study, the botanicals used only they were effective but when they were used in combination they show less effective so it is evident that as extract was diluted, toxicity was decreased resulting in correspondent decrease in inhibition and any inhibition was observed in distilled water.…”
Section: In Vitro Effect Of Botanicals and Trichoderma Harzianum Agaimentioning
confidence: 99%
“…It was found that the gelatinous matrix enables fungal attachment and enhances parasitic abilities of most isolates, which could also utilize it as a nutrient source (Sharon et al, 2009). The conidia of Trichoderma attach to nematode cuticle or to egg shell and parasitize on them (Sharon et al, 2007). Al Kader (2008) reported a high nematicidal effect of the fungus Paecilomyces lilacinus culture filtrate on J 2 of M. incognita, with 99% of J2 immobilized after 2 days of treatment.…”
Section: Introductionmentioning
confidence: 99%
“…In their studies, Samuels et al [9] reclassified many widely used "T. viride" strains as T. asperelloides. Some of the extensively used strains that have been reclassi *Address correspondence to this author at the Crop Protection Division, Central Institute for Cotton Research, Nagpur 440010, India; Tel: +91-7103-275538; Fax: +91-7103-275529; E-mail: prasunmukherjee1@gmail.com fied are T. harzianum T103 [10], T. asperellum T44 [11], T. viride ATCC 52439 and TR 31 [12]. T. viride strain, isolated and developed at the Tamil Nadu Agricultural University, Coimbatore, India [13] is the most popular biofungicides approved by the Central Insecticides Board (CIB), Govt.…”
Section: Introductionmentioning
confidence: 99%